2021
DOI: 10.3390/nu13051564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Milk on Very Preterms’ Gut Microbiota and Alkaline Phosphatase Activity

Abstract: The FEEDMI Study (NCT03663556) evaluated the influence of infant feeding (mother’s own milk (MOM), donor human milk (DHM) and formula) on the fecal microbiota composition and alkaline phosphatase (ALP) activity in extremely and very preterm infants (≤32 gestational weeks). In this observational study, preterm infants were recruited within the first 24 h after birth. Meconium and fecal samples were collected at four time points (between the 2nd and the 26th postnatal days. Fecal microbiota was analyzed by RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
4
10
1
Order By: Relevance
“…As recently proposed by our group, ALP activity may have increased due to the increased production of butyrate. 21 Butyrate is well-known to induce ALP activity and although no specific changes in butyrate-producing bacteria were observed in the present study after the consumption of nonalcoholic and alcoholic beer, since fecal concentrations of short chain fatty were not measured, this hypothesis cannot be ruled out. Increased fecal ALP activity may be indicative of improved intestinal barrier function, since ALP dephosphorylates lipopolysaccharide which contributes to reduce inflammation and intestinal permeability.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…As recently proposed by our group, ALP activity may have increased due to the increased production of butyrate. 21 Butyrate is well-known to induce ALP activity and although no specific changes in butyrate-producing bacteria were observed in the present study after the consumption of nonalcoholic and alcoholic beer, since fecal concentrations of short chain fatty were not measured, this hypothesis cannot be ruled out. Increased fecal ALP activity may be indicative of improved intestinal barrier function, since ALP dephosphorylates lipopolysaccharide which contributes to reduce inflammation and intestinal permeability.…”
Section: Discussioncontrasting
confidence: 69%
“…When analyzing the activity of ALP in fecal samples, we observed that both nonalcoholic and alcoholic beer tended to increase fecal ALP activity. As recently proposed by our group, ALP activity may have increased due to the increased production of butyrate . Butyrate is well-known to induce ALP activity and although no specific changes in butyrate-producing bacteria were observed in the present study after the consumption of nonalcoholic and alcoholic beer, since fecal concentrations of short chain fatty were not measured, this hypothesis cannot be ruled out.…”
Section: Discussionsupporting
confidence: 44%
“…Most studies exploring enteral feeding and the GI microbiota of VLBW infants categorize infants based on their predominant enteral feeding source throughout hospitalization (Cai et al, 2019;Ford et al, 2019;Morais et al, 2021;Parra-Llorca et al, 2018;Pin ˜eiro-Ramos et al, 2021;Wandro et al, 2018;Wang et al, 2020;Xu et al, 2018), rather than examining a dose prior to each stool, making comparisons with this present analysis more difficult. However, mother's milk has generally been associated with higher alpha-diversity (Ford et al, 2019;Morais et al, 2021;Xu et al, 2018;Zanella et al, 2019) and shifts in beta-diversity (Cai et al, 2019;Ford et al, 2019;Parra-Llorca et al, 2018;Pin ˜eiro-Ramos et al, 2021;Wang et al, 2020;Xu et al, 2018;Zanella et al, 2019), similar to our findings. This may result from the complex microbial communities present in preterm mother's milk that can contribute to GI colonization in infants (Asbury et al, 2020;Biagi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…have been found to increase the fecal microbiota of preterm infants fed with breastmilk and human donor milk during the first three months of life [ 116 ]. In a study conducted to examine the effect of breastmilk, donor human milk or formula on shaping the fecal microbiota of preterm infants during the first month of life, infants fed with mother’s own milk have higher fecal SCFA-producing bacteria compared with those fed donor human milk or formula [ 117 ]. A previous study found that breastmilk influences the microbial colonization of preterm infants over the first 30 days of life.…”
Section: Effects Of Feeding Types On Gut Microbiota and Its Metabolit...mentioning
confidence: 99%